DINAMIKA PARTISIPASI PUBLIK DALAM DEMOKRASI DIGITAL: STUDI KASUS GERAKAN #GEJAYANMEMANGGIL TAHUN 2019 - Mujahidah, Nailah Alifah; Maulidza, Raisha; Sabilla, Najwa (Indonesian Democracy Research Center, 2024)
This research explores digital democracy through a case study of the #GejayanMemanggil Movement in 2019. The Gejayan Movement was originally initiated in 1998 as a form of movement during the reformation era. But now, the movement reappeared in 2019, which was initiated by Yogyakarta area students to voice their aspirations regarding government policies. Then the action carried out by Yogyakarta area students became a highlight on social media, so #gejayanmemanggil was present as a form of support from the Indonesian people who participated in voicing through social media, so that #geyanmemanggil became a trending topic on Twitter social media in 2019. This research uses a qualitative analysis method, from internet sources such as scientific articles, journals, and relevant and accredited books. This research highlights the role of social media in shaping public opinion and mobilizing participation. It focuses on millennials and Z generations who actively use digital platforms to voice their aspirations and build collective awareness. Transparent government responses and information disclosure are identified as key to maintaining stability and increasing public trust in an era of digital democracy.